A Critical Analysis of Terminological Prejudices of Western Media on Islam: ISLAMOPHOBIA AND ITS IMPACT ON RELATIONS BETWEEN ISLAMIC AND WESTERN CIVILIZATIONS (Khairulummah, 2022)
In the last few decades, the Western media has waged a war against the identity to victims of the followers of Islam. The media is being used as a tool to create widespread excitement and misunderstanding in the of Islamophobia. When reporting crimes and terrorism in the media, Islamic terms are used in such a way, which create a negative impression about Islam. These terms are removed from the religious context in such a way that their original meanings and concepts go into the background and new meanings created by the media become popular. Similarly, misleading statements and misrepresentations made in the media to spread fear against Muslims are commonly known as 'Islamophobia'. The bias of the Western media: The general concept of Islam propagated by the media houses states that "all believers in Islam are one and the same". Separation,  walling and defaming Muslims around the world. This general conception of Islam is a creation of Western Orientalism, which makes non-Western cultures contradict the West. Following this Orientalism, Muslims are portrayed as alien, strange, backward and irrational groups. This can be observed when a Muslim is found to be involved in a crime, while the majority of Muslims show disengagement from his crime, but still the entire Muslim Ummah should be forcibly linked to that person's crime. Within Islam, there are many schools of thought, diverse populations and individuals and groups with diverse cultures, which can be called a Muslim Ummah in terms of basic beliefs and faith, but they cannot be brought into a general identity in any way. ۔ No other person in the world can be held responsible for the actions of an individual or a group of individuals. But while giving a general identity to all the followers of Islam, the media blames the entire Ummah for the actions of an individual or a few individuals, it is an attack on the religious identity of all Muslims as well as the accused. This article is an attempt to describe a critical analysis of Prejudicial Attacks on Islam on the Western Media.